A Review On Ethnomedicinal Claims Of Acanthospermum Hispidum DC - Patel , Mital A; Patel, Bhupesh; Pandya, Preeti (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Plants are of immense value to human health and roughly 80% of world’s population relies on them for cure of various diseased conditions. The aim of present review was to provide the all available ethnomedicinal information and research updates pertaining to Acanthospermum hispidum DC. Materials and Methods: Information regarding ethnomedicinal claim were reviewed by using the available books with especial reference to medicinal plants compiled from books on ethnobotany and research articles available on internet till date. The obtained Information were categorized as per vernacular names, locality, used parts, therapeutic claims, type and mode of administration along with ingredients and dosage forms of the preparations. Results: Acanthospermum hispidum DC. is annual herb in the family Asteraceae, which is native to central and south America, reported in 60 countries and moist habitat throughout India. This plant used as traditional medicine for various disease condition. All parts of plants are used for medicinal purpose through both the routes i.e external and internal. Conclusion: Acanthospermum hispidum DC. conducting provable scientific studies (pharmacological and clinical) were needed to establish its multiple ethnomedicinal claims.